PENERAPAN MODEL PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII SMPIT AN-NIDA’ LUBUKLINGGAU - Henria, Aprin; Fauziah, Anna; Refianti, Rani (Linggau Journal Science Education (LJSE), 2025)
This study aims to determine the improvement of students' problem-solving skills in mathematics learning after being applied using the problem solving model. The type of research used is fre Experimental design. The population of all students in grade VIII of SMP IT An-Nida Lubuklinggau amounted to 119 students and as a sample of class VIII.3 which amounted to 29 students on the number pattern material, sampling was carried out randomly, data collection was carried out by technical test the collected data was analyzed using the t-test at a significant level = 0.05. Based on the results of the analysis of the final test data, it can be concluded that there is an improvement in the mathematical problem-solving ability of grade VIII students of SMP IT An-nida Lubuklinggau after the problem solving model is applied. The average score of students' mathematical problem-solving ability from the student's pre-test score was 77.33 while the student's post-test score was 84.43.